Heterogeneity and persistence in tax responsiveness: Evidence from owner-managed companies - Gabriella Massenz (Research Institute of Industrial Economics (IFN), 2024)
We study responsiveness of owner-managed companies to a corporate income tax kink using Dutch tax records linking firms to their owners. The corporate taxable income elasticity (CETI) is 0.08, but tax sensitivity is over three times higher for firms using specific investment deductions. These are generous, allow for large depreciation and include assets that can reflect owner-managers' consumption. The CETI rises with deductions' use and is higher for large firms in industries with easy access to them. We document persistence at the kink, which is driven by large firms using deductions and whose owner-managers repeatedly target personal income tax kinks.
Keywords: H24; H25; H26; H30; 330; taxable income elasticity; owner-managed companies; tax deductions; bunching